Generation of biological hypotheses by functional imaging links tumor hypoxia to radiation induced tissue inflammation/glucose uptake in head and neck cancer. (February 2021) - Zschaeck, Sebastian; Zöphel, Klaus; Seidlitz, Annekatrin; Zips, Daniel; Kotzerke, Jörg; Baumann, Michael; Troost, Esther G.C.; Löck, Steffen; Krause, Mechthild
Highlights: PET measured tumor hypoxia is inversely correlated with PET measured glucose uptake of tumor surroundings especially during radiotherapy. Both parameters bear great prognostic value. The prognostic accuracy can be improved when both parameters are combined. PET examinations during radiotherapy can unravel complex tumor-host interactions. Abstract: Background and purpose: Positron emission tomography (PET) is a functional imaging modality which is able to deliver tracer specific biological information, e.g. about glucose uptake, inflammation or hypoxia of tumors. We performed a proof-of-principle study that used different tracers and expanded the analytical scope to non-tumor structures to evaluate tumor-host interactions. Materials and methods: Based on a previously reported prospective imaging study on 50 patients treated with curative intent chemoradiation (CRT) for head and neck squamous cell carcinoma, PET-based hypoxia and normal tissue inflammation measured by repeat 18F-fluoromisonidazole (FMISO) PET and 18F-fluorodesoxyglucose (FDG) PET, respectively, were correlated using the Spearman correlation coefficient R. PET parameters determined before and during CRT (week 1, 2 and 5), were associated with local tumor control and overall survival. Results: Tumor hypoxia at all measured times showed an inverse correlation with mid-treatment FDG-uptake of non-tumor affected oral (sub-)mucosa with R values between −0.35 and −0.6 (all p  < 0.05). Mucosal FDG-uptake and mucosal hypoxia correlated positively but weaker (R values between 0.2 and 0.45). More tumor hypoxia in FMISO-PET (week 2) and less FDG-uptake of (sub-)mucosa in FDG-PET (week 4) were significantly associated with worse LC (FMISO TBRpeak : HR = 1.72, p  = 0.030; FDG SUVmean : HR = 0.23, p  = 0.025) and OS (FMISO TBRpeak : HR = 1.71, p  = 0.007; FDG SUVmean : HR = 0.30, p  = 0.003). Multivariable models including both parameters showed improved performance, suggesting that these modalities still bear distinct biological information despite their strong inter-correlation. Conclusion: We report first clinical evidence that tumor hypoxia is inversely correlated with increased FDG-uptake during radiation, potentially expressing inflammation. This observation merits further research and may have important implication for future research on tumor hypoxia and radio-immunology. Our study demonstrates that functional imaging can be utilized to assess complex tumor-host interactions and generate novel biological insights in vivo vero .